Rhizoglomus intraradices Improves Plant Growth, Root Morphology and Phytohormone Balance of Robinia pseudoacacia in Arsenic-Contaminated Soils - Zhang, QiaoMing; Gong, Minggui; Liu, Kaiyang; Chen, Yanlan; Yuan, Jiangfeng; Chang, Qingshan (Frontiers in Microbiology, 2020)
Arbuscular mycorrhizal fungi (AMF) are known to improve the resistance of host plant against various heavy metal stresses. However, the Arsenic (As) resistance mechanism of AMF-inoculated woody legumes remains unclear. In this study, black locust (Robinia pseudoacacia L.) seedlings were cultivated in potted soils inoculated with or without AMF Rhizoglomus intraradices under three different levels of As stress (0, 100 and 200 mg As kg-1 soil) over four months. The objective of this paper was to investigate the effects of AMF on plant growth, root morphology, content and ratio of endogenous phytohormones and soil glomalin under arsenic (As) stress condition. As stress toxicity suppressed the AM spore germination and colonization, plant growth and the content of soil glomalin, and changed the morphological characteristics of roots and the balance of endogenous hormone level in plants. However, R. intraradices-inoculation improved the shoot and root dry weight, total root length, root surface area, root volume, number of root forks and tips across all As treatments. R. intraradices inoculation obviously decreased the percentage of root length in 0-0.2 mm diameter class, it increased those in 0.5-1.0 mm and >1.0 mm diameter classes, and the percentages in 0.2-0.5 mm diameter class were less affected by R. intraradices inoculation. The concentrations of easily extractable glomalin-related (EE-GRSP) and total glomalin-related soil protein (T-GRSP) were higher in rhizosphere soils of R. intraradices inoculated seedlings than those in rhizosphere soils of non-inoculated seedlings. Furthermore, R. intraradices inoculation increased the concentrations of indole-3-acetic acid (IAA) and abscisic acid (ABA), but decreased the concentrations of gibberellic acid (GA) and zeatin riboside (ZR). The phytohormone ratios of IAA/ABA, GA/ABA, ZR/ABA, and (IAA+GA+ZR)/IAA in R. intraradices-inoculated seedlings were lower than those in non-inoculated seedlings. These results indicated that R. intraradices alleviated As toxicity in R. pseudoacacia seedlings by improving their plant growth, altering root morphology, regulating the concentration and ratio of phytohormones and increasing the concentration of soil glomalin. The results suggested that AMF-inoculated R. pseudoacacia seedlings would be a critical factor in successful vegetation restoration and soil development in As-contaminated soils.